PERILAKU POSITIF DAN NEGATIF TOKOH DALAM NOVEL â€œAYAT-AYAT CINTAâ€ KARYA HABIBURRAHMAN EL SHIRAZY (SUATU PENDEKATAN SOSIOLOGI) - Mulyani, Wahyu (Jurnal Penelitian Humaniora, 2014)
Habiburrahman El Shirazy is a novelist who can captivate the public through his work entitled ?Ayat-Ayat Cinta?. This novel was written based the social environment and the characters behave as if in everyday real life. Most of the stories of this novel was based on Islamic perspective but universal since its setting was in Islamic state, Cairo Egypy. Purpose of this paper was to describe (1) the positive perilaku of the characters such as Fahri, Maria, and Aisah based on sosiological approach; (2) to describe the negative perilaku of Noura Bahadur based on the sociological approach. The method used was descriptive qualitative, a method that systematically describe the facts about the positive and negative perilaku of the characters. The approach used was memesis sociology and pragmatic sociology. The results showed that the positive perilakus of Fahri, Maria, and Aisha. Fahri was wise, kind, helpful, obedient worshiper, and posi tive. Maria was a respectful, helpful, and kind. Aisha was helpful, honest, kind, and considerate. Negative perilaku was shown in figures such as Noura and Bahadur. Bahadur has was a rapists with nasty character while Noura liked was gossipping and haerdharted.